Fungsi Masjid Terhadap Pengelolaan Pengembangan Masyarakat Islam (Pengembangan Keumatan) - Rahmat Hidayat (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2019)
The mosque has a very large role and function in all dimensions of Muslim life. Where the mosque is a symbol that illustrates the strength map of the people and can unite and realize every meaning of goodness. Without mosque, the unity of the Muslims will be easily broken even divorced. The mosque is not just a place of worship, but all aspects of life problems of the people and the development and fostering of the community (people) of Islam can be resolved from the mosque. However, Along with the times, the mosque experienced a shift in values, where the mosque is no longer functioned as a function that has been exemplified by the Prophet Muhammad Saw. Based on this concern, some Muslims are aware and care about the condition of the mosque that began to be abandoned by the people, and it can be realized that lately there have been emerging movements that have encouraged the functioning of the mosque as it was in the early days of Islam. As an effort in managing the mosque by implementing several functions such as: planning, organizing, leadership actualization, supervision and evaluation become a structured management process. And this matter is combined with the development of human rights or the development of Islamic society. Awareness of the people of worship hereafter and balancing faith in worldly worship (capacital social).